EFFECT OF PROBLEM SOLVING LEARNING MODEL ON STUDENTS ACHIEVEMENT - Damopolii, Insar; Nunaki, Jan Hendriek; Supriyadi, Gatot (Journal of Education Reseach and Evaluation, 2018)
This research aims to determine the difference in student achievement that used problem solving learning model and conventional learning model. The type of research was quasi experimental. The research was conducted at SMP N 11 Manokwari. The sampling technique used purposive sampling. A number of the sample the control group of 31 students and the experimental group of 30 students. Data analysis used independent t-test at significant level 0,05 with help of SPSS 22 for Windows program. The results showed that there was a difference in the student achievement (P = 0,000 <0.05), where the N-Gain value of experimental group was 0.4 and the control group was 0.3. The conclusion, there is a difference in the improvement of student achievement, where the students who learn by using the problem solving learning model higher the improvement of student achievement compared to the students who learn by using the conventional learning model.